Yoga Program for Type 2 Diabetes Prevention (YOGA-DP) Among High-Risk People: Qualitative Study to Explore Reasons for Non-participation in a Feasibility Randomized Controlled Trial in India - Mishra, Pallavi; Greenfield, Sheila Margaret; Harris, Tess; Hamer, Mark; Lewis, Sarah Anne; Singh, Kavita; Nair, Rukamani; Mukherjee, Somnath; Krishnamurthy Manjunath, Nandi; Harper, David Ross; Tandon, Nikhil; Kinra, Sanjay; et al. (Frontiers in Public Health, 2021)
Background Yoga-based interventions can be effective in preventing type-2 diabetes mellitus (T2DM). We developed a Yoga programme for T2DM prevention (YOGA-DP) among high-risk people and conducted a feasibility randomised controlled trial (RCT) in India. The objective of this study was to identify and explore why potential participants declined to participate in the feasibility RCT. Methods An exploratory qualitative study, using semi-structured interviews, was conducted at a Yoga centre in New Delhi, India. Fourteen people (10 women and four men) who declined to participate in the feasibility RCT were interviewed, and 13 of them completed the non-participant questionnaire, which captured their socio-demographics, diet, physical activity, and reasons for declining. Results Three types of barriers were identified and explored which prevented participation in the feasibility RCT: (1) personal barriers such as lack of time, perceived sufficiency of knowledge, preferences about self-management of health and trust in other traditional and alternative therapies; (2) contextual barriers such as social influences and lack of awareness about preventive care; and (3) study-related barriers such as lack of study information, poor accessibility to the Yoga site and lack of trust in the study method and intervention. Conclusions We identified and explored personal, contextual, and study-related barriers to participation in a feasibility RCT in India. The findings will help to address recruitment challenges in future Yoga and other RCTs.